Uma (re) leitura de textos publicitários multimodais em outdoor a partir da gramática do design visual - Carregosa, Sebastião Andrade (2019)
This work brings as object of research the study of the interactional metafunction in multimodal advertising texts in outdoors. While it has as main objective to show how the Grammar of Visual Design (GVD) (Kress; van Leeuwen, 2006) can contribute to the Portuguese Language teaching, in what refers to the study of the discursive elements of visual representation in a multiletration perspective, from the analysis of Multimodal Advertising Texts. This is because, according to Kess and van Leeuwen (2006), it is of fundamental importance to create a method of analysis to study the semiotic resources of multimodal texts – constituted by different codes, in this case, the verbal and the visual – to the preparation of the GVD. In this context, the Pedagogy of Multiletrations (New London Group, 1996), corroborates with the proposal of the GVD in the sense that, according to Rojo, it is necessary to work the multiple literatures, not just the verbal one, because multimodality refers to the approach of a semiotic system, from which communication and the representations of meanings take into account the use of varied resources – the image, video, audio etc. The need for this research emerges from the worrying scenario of basic education pointed out by the National Institute of Educational Studies and Research (Inep) in 2015, whose students had low results, in addition to data from the International Student Assessment Program (Pisa) of the same year, which shows a drop in reading position according to the world ranking – 59th position from a total of 70 countries surveyed. In addition, we can observe that with the access of the students to the new technologies, these are exposed more and more to multimodal advertising texts. However, the school context often assigns little relevance to the systematic study of multimodal texts. In this perspective, in the light of the authors’ conceptions, this proposal used as a methodology the theoretical research, through bibliographic studies, the observation, the application of questionnaires, as well as the accomplishment of five workshops that include activities of reading and interpretation of advertising texts. After the workshops, the results were analyzed and interpreted qualitatively, from the perspective of a case study, evidencing that the present study contributes to the improvement of the Portuguese Language teachers’ performance in relation to pedagogical posture and students reading practices from a multiletration perspective, bringing as final product a Pedagogical Notebook that can be consulted by managers, coordinators, teachers, students and researchers in the Language and Linguistics areas.